A Comprehensive Analysis of Glycemic Variability and Time in Ranges Assessed using CGM in Diabetic People with Microvascular Complications: A Single-Center Retrospective Real-World Evidence Study on Indian Population. Issue 1 (2022) - Sabharwal, Mudit; Palukuri, Srivani; Deka, Saurav
No abstract available